Ten Years after The Global Economic Crisis: A Retrospective Analysis - Magas, István (Public Finance Quarterly, 2023)
The study attempts to take stock of the crisis management measures taken during the global economic crisis between 2008 and 2011, draw macroeconomic conclusions from it and identify the uncertainties and the old-yet-new risks still persisting at the end of 2018. The most important conclusion is that while both economic conditions and financial systems were able to stabilize in the most developed countries of the world economy, it cannot be claimed with full certainty that all risks that had previously led to a recession were able to be handled properly. While quantitative easing (QE) and discretionary fiscal policies in both the USA and the EU restored normalcy in the business cycle, neither productive investments nor labor or total factory productivity were able to return to the growth trends experienced before the crisis.